Answer:
a
Step-by-step explanation:
if you plug 4 in for x it solves it
Answer:
Step-by-step explanation:
<u>Given recursive formula</u>
- a₁ = 0
- aₙ = 2(aₙ₋₁)² - 1, for n>1
<u>The first 5 terms are:</u>
- a₁ = 0
- a₂ = 2(0)² - 1 = 0 - 1 = -1
- a₃ = 2(-1)² - 1 = 2 - 1 = 1
- a₄ = 2(1)² - 1 = 2 - 1 = 1
- a₅ = 2(1)² - 1 = 2 - 1 = 1
38 esa es la respuesta a mi me deio eso suerte
x = 0.25
Step-by-step explanation:
8x = 2
x = 2/8
x = 0.25
Answer:
G) -12
Step-by-step explanation:
x is increasing by 2
y is decreasing by 24
-24 / 2 = -12